UPAYA MENINGKATKAN HASIL BELAJAR IPS PADA MATERI TOKOH PERJUANGAN MELALUI ROLE PLAYING BAGI SISWA KELAS V SEKOLAH DASAR - Sri Suryani; Yanti Karyanti Wihardis; Siti Rohmah (CV Putra Publisher, 2023)
The success of a teaching and learning process can be seen from the level of students' mastery of the material being taught. If as part of the students have mastered the material, it can be seen that the teaching and learning process has been successful. With regard to the teaching and learning process itself, the authors see the fact that there are still many elementary school students, especially fifth grade students at SDN 2 Cidatar who experience difficulties in social studies learning, one of the reasons being that the teacher is not optimal in choosing the learning method used. Learning Social Sciences is inseparable from the tendency of the teacher centered learning process. Such conditions make the learning process only controlled by the teacher. Regarding the not yet optimal social studies learning outcomes for class V SDN 2 Cidatar in terms of efforts to improve student learning outcomes, the authors seek to apply the Role Playing learning model as an alternative meaningful learning that leads to active, creative, effective, and fun learning. The purpose of this classroom action research is to find out whether the application of the role playing method can improve student learning outcomes and can also make it easier for students to understand the material to improve student learning outcomes in social studies learning. This classroom action research was carried out in 2 cycles. Each cycle contained four stages, namely planning, implementing, observing and reflecting. The method used in this study refers to Kurt Lewin's model which consists of four main components of class research namely planning, implementation, observation and reflection. Data analysis in this classroom action research used quantitative and qualitative analysis of social studies learning outcomes in the analysis starting from cycle 1 and cycle 2 to be compared with percentage descriptive techniques. After applying the Role Playing method in social studies learning on the material to improve student learning outcomes, students understand more about this material. This can be proven in increased student learning outcomes. the lowest cycle I was 40 Cycle II was 66, the average value of cycle I was 68.2 cycle II was 78.4 and the learning mastery of cycle I was 67%, and cycle II was 100%. The suggestions that can be given are: (1) The teacher should be more creative in choosing various methods that suit the demands of the needs and circumstances of the students and the characteristics of the subject matter to be delivered. (2) Role playing learning is an alternative that deserves to be developed to overcome the problem of low learning outcomes in elementary schools.